Dehydroepiandrosterone sulfate and fall risk in older people: Sex differences in the Pro.V.A. longitudinal study. (October 2019) - Carrer, Pamela; Trevisan, Caterina; Franchin, Alessandro; Volpe, Elisabetta Della; Rancan, Andrea; Zanforlini, Bruno Micael; Maggi, Stefania; Noale, Marianna; Corti, Maria Chiara; Perissinotto, Egle; Manzato, Enzo; Sergi, Giuseppe
Highlights: We investigated the association between dehydroepiandrosterone sulfate (DHEA-S) and fall risk in older men and women. A higher level of DHEA-S was associated with reduced odds of recurrent falls. The association between DHEA-S and falls seemed to be stronger in older women than in older men. Abstract: Background: The effect of dehydroepiandrosterone sulfate (DHEA-S) on fall risk in older age is still unclear, as is the effect of sex on any relationship between the two. Our aim was to evaluate the association between DHEA-S and the risk of falls and risk of recurrent falls in community-dwelling older men and women. Methods: We included 1949 (781 M, 1168 F) older adults enrolled in the Progetto Veneto Anziani study. Baseline serum DHEA-S levels were analyzed by immunoassay. The number of falls reported in the year preceding the 4.4-year follow-up assessment was collected. The association between DHEA-S and falls was analyzed by multinomial logistic regression, adjusting for potential confounders and considering death as alternative outcome. Results: After the follow-up, 548 (36.8%) individuals reported at least one fall in the previous year, and 214 (14.4%) reported ≥2 falls (recurrent falls). Each 1-standard deviation (SD) increase in log-transformed DHEA-S level reduced the odds of experiencing at least one fall by 9% (95%CI:0.88-0.95), and the risk of recurrent falls by 16% (95%CI:0.79-0.89). The highest DHEA-S tertile was 27% (95%CI:0.65-0.83) less likely to experience recurrent falls than the lowest tertile. The analyses, stratified by sex, suggested a strong association between DHEA-S and the fall risk for women (OR = 0.91; 95%CI:0.87-0.95 for at least one fall; OR = 0.83, 95%CI:0.78-0.89 for recurrent falls per each 1-SD increase in log-transformed DHEA-S); non-significant results were observed among men. Conclusions: Higher levels of DHEA-S are associated with a lower risk of falls and recurrent falls in older people, especially women.